Pelatihan Keluarga Lansia ( BKL) Dalam Meningkatkan Kesehatan Gigi Lansia - Ainun Mardiah; Cut Aja Nuraskin (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Elderly is a process of changing the function of body tissues and organs, there is a decrease in the ability of various body tissues. The decrease in this condition occurs in various organs of the body, including weakened memory, sensory changes, and changes in dental and oral health. Dental and oral problems can affect the nutritional status and health of the elderly. The number of malnourished elderly in Indonesia is 3.4% and 96% of the elderly experience dental caries. Seeing this phenomenon, the health of the elderly needs to be improved, especially dental and oral health so that there is a nutritional balance and affects the general condition of the elderly. This is the background for the service team to provide training on "Improving behavior change and the role of families who have the elderly". This activity was held in the village of Kayee Leu, Aceh Besar, with preventive and promotive methods. The participants were 30 people, namely elderly cadres and families. The activity lasts for 1 day with a duration of 4 (four) hours. Through this activity, it is hoped that the skills and understanding of participants who have elderly people will increase. Keywords: Training, cadres, health, teeth, elderly